Risk perception in forest utilizations: experimental analysis in the Basilicata forest sites. - D. Cardinale; P. D’Antonio; N. Moretti; Vincenzo Nunzio Scalcione (IJRDO Journal of Forestry, wild life and Environment, 2020)
The present legal framework for the protection of health and safety in the workplace, established by Legislative Decree 81/2008, has identified the “work-related stress” as one of the risks to be assessed, according to the contents of European Agreement of 8 October 2004, and the importance of its management. The present analysis deals with an important subject as the workplace safety, in particular the risk perception and the work-related stress of the operators in the agro-forestry sector. The sampling plan was based on the delivery of structured questionnaire (n= 378, 171 women and 207 men). Results showed that the accident and safety sector cannot be and should not be considered only as a repressive instrument to identify specific violations or responsibilities to be punished. It must instead be considered as a tool for better identifying measures and strategies to eliminate or to minimise the risk perception and the work – related stress in the same or in a similar working environment.